(NsOEDINENIQ TRANSURANOWYH \LEMENTOW (B/s - (NmEFODXEWA(B, (NmAJQ pAWLOWNAs; (NkROT(B, (NnIKOLAJ nIKOLAEWI^s; (NiNSTITUT FIZI^ESKOJ HIMII an sssrs ((NmOSKWA (B:s (NnAUKA(B,s, 1987)
(NbIBLIOGR(B. (NW KONCE GLAWs
(Nan sssr(B, (NiN(B-(NT FIZ(B. (NHIMIIs
Keywords: (NtRANSURANOWYE \LEMENTY(B, (NSOEDINENIQs -- (NhIMIQs